2014
DOI: 10.1016/j.jvs.2013.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative smoking is associated with early graft failure after infrainguinal bypass surgery

Abstract: Although nonsmokers were significantly older, had more comorbidities, and required more distal revascularization, active smokers still had an increased risk for development of early graft failure. These results stress the need for immediate smoking cessation before lower extremity bypass. Further research is warranted to determine an optimal period of abstinence among smokers with peripheral arterial disease to reduce their risk for early graft failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 34 publications
2
41
0
3
Order By: Relevance
“…A few prior studies have reported variable outcomes following revascularization in diabetic cohorts, but nearly all are based on heterogeneous populations undergoing either endovascular or open revascularization at a range of anatomic levels for a wide variety of indications. 15,[19][20][21][22][23] These data are often used to extrapolate projected outcomes following infrageniculate PVI or open bypass interventions, but to date there is no level I evidence regarding major outcomes for either of these procedures within the diabetic population. 24,25 In our study, endovascular interventions had better 1-year primary patency than open bypasses both overall and within the diabetic population, with similar rates of major amputation and death.…”
Section: Discussionmentioning
confidence: 99%
“…A few prior studies have reported variable outcomes following revascularization in diabetic cohorts, but nearly all are based on heterogeneous populations undergoing either endovascular or open revascularization at a range of anatomic levels for a wide variety of indications. 15,[19][20][21][22][23] These data are often used to extrapolate projected outcomes following infrageniculate PVI or open bypass interventions, but to date there is no level I evidence regarding major outcomes for either of these procedures within the diabetic population. 24,25 In our study, endovascular interventions had better 1-year primary patency than open bypasses both overall and within the diabetic population, with similar rates of major amputation and death.…”
Section: Discussionmentioning
confidence: 99%
“…Given the known association between smoking and early graft failure, the differential rates of surgical bypass are likely related to physician decision making. 25 A larger study would likely be necessary to detect significant differences in rates of major amputation among patients who quit vs continued smoking.…”
Section: Discussionmentioning
confidence: 99%
“…1), but they had a similar 12-month reintervention rate, and better amputation-free survival. Whereas, in the study by Vierthaler and the members of the Vascular Study Group of New England [7], among other BTK -below-the-knee procedure; CAD -coronary artery disease; CHF -congestive heart failure; CI -confidence interval; INR -international normalized ratio for prothrombin time; LDL -low-density lipoprotein; MPV -mean platelet volume; TASC -Trans-Atlantic Inter-Society Consensus; TLR -target lesion revascularization However, according to the study by Selvarajah et al [31] and widely accepted knowledge [1][2][3]9], active smokers had an increased risk of LLI progression and the failure of its treatment, pharmacologically, endovascularly and surgically. Our analysis showed the favourable effect of consecutive endovascular procedures on amputation delay, but also revealed that loss of primary stent patency (expressed by the need for TLR) or the absence of stent implantation led to worse outcomes (Tab.…”
Section: Discussionmentioning
confidence: 99%